1988
DOI: 10.1017/s003329170000787x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric complications and schizophrenia: a computed tomographic study

Abstract: SynopsisAll patients aged 16–50 years who had been discharged from the Maudsley Hospital over a 4-year period with a diagnosis of schizophrenia were ascertained retrospectively. Case records were rated blindly for a history of obstetric complications (OCs). Sixty-one patients who satisfied the RDC for schizophrenia had undergone CT scanning. Those with a definite history of OCs presented at an earlier age. In this group widening of cortical sulci and fissures was more strongly correlated with VBR than in subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 31 publications
4
38
0
Order By: Relevance
“…The present study is a case-control whereas the above mentioned one was a cohort study. However, in this case the sample size was larger, the overall assessment was based on a validated scale [6], and diagnoses were based on more restrictive diagnostic criteria. Furthermore, following the recommendations of previous studies, the risk measure was controlled for two likely confounding variables, SES and FPH, because of their FPH family psychiatric history, 2 SES Socio-economic status a Crude odds ratio (OR), 95% confidence intervals (CI), and statistical significance (P).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is a case-control whereas the above mentioned one was a cohort study. However, in this case the sample size was larger, the overall assessment was based on a validated scale [6], and diagnoses were based on more restrictive diagnostic criteria. Furthermore, following the recommendations of previous studies, the risk measure was controlled for two likely confounding variables, SES and FPH, because of their FPH family psychiatric history, 2 SES Socio-economic status a Crude odds ratio (OR), 95% confidence intervals (CI), and statistical significance (P).…”
Section: Discussionmentioning
confidence: 99%
“…The Lewis-Murray scale of obstetric data (OCS) [6] was administered to parents. This is a scale administered by the clinician that retrospectively rates information on obstetric complications from medical records, birth records, and maternal interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, there is little doubt that obstetric complications are associated with later schizophrenia; whether these (detectable) obstetric events are of aetiological importance in themselves, or whether they are themselves a consequence of earlier (undetectable) events, is unclear. What is undisputed is that schizophrenics with a history of obstetric complications present earlier than those without such a histori (De Lisi et al 1987;O'Callaghan et al 1988;Owen et al 1988); and a number of studies have shown that such patients are more likely to exhibit ventricular enlargement Murray et al 1988;Lewis et al 1988;Pearlson et al 1989), though not all have concurred (Nimgoankar et al 1988). …”
Section: Structural Brain Abnormalitiesmentioning
confidence: 99%
“…In schizophrenic populations, males are more likely to have a history of obstetric complications than are females (Pearlson et al 1985;Wilcox & Nasrallah, 1987;Owen et al 1988;Foerster et al 1991ft). This is consonant with the fact that structural brain anomalies have been reported more commonly in male than female schizophrenics (see Table 1).…”
Section: Brain Abnormalities In Schizophrenic Malesmentioning
confidence: 99%
“…intrauterine environmental stresses such as influenza exposure; Mednick et al 1988;O'Callaghan et al 1991;Takei et al 1996), at birth (e.g. obstetrical complications; Owen et al 1988) and/or during childhood is critical. The neurodevelopmental hypothesis of schizophrenia is based on the notion that these early-life environmental factors can have significant consequences for processes of brain maturation.…”
Section: Introductionmentioning
confidence: 99%